Impacts of Climate Change on Brazilian Agriculture : Refocusing Impact Assessments to 2050 - World Bank (Washington, DC, 2013)
This report evaluates the requirements for an assessment of climate change impacts on agriculture to guide policy makers on investment priorities and phasing. Because agriculture is vital for national food security and is a strong contributor to Brazil's GDP growth, there is growing concern that Brazilian agriculture is increasingly vulnerable to climate variability and change. To meet national development, food security, climate adaptation and mitigation, and trade goals over the next several decades, Brazil will need to significantly increase per area productivity of food and pasture systems while simultaneously reducing deforestation, rehabilitating millions of hectares of degraded land, and adapting to climate change. There is inadequate data to accurately model projected climate challenges facing Brazil. The report concludes that key integrated and linked interventions are needed in the short term to significantly improve currently available assessments of climate change impact on Brazilian agriculture and to guide policy makers with the priorities and phasing of needed investments.